Երևանի թանգարանների դասակարգումը և ինտերիեր դիզայնը ըստ պրոՖիլների - Աճառյան, Անի
In the article in classified order are presented the main principles of museum interior design with their profiles, in addition the classified order of existing 40 museums in erevan is presented. Included museum profiles accordingly are the followings: art, historical and archeological, natural, technical, memorial, architectural, complex as well as site museums of monuments and expeditions. The main principles of museum interior design vary definitely in each profile and demand different design approaches to provide required functions. overall, from functional view profiles dictate the presentation, preservation, safety, direction planning and many other professional skills that play important role in complete design making. Thus, for planning correct museum interior design the best examples of each museum profile in the world are provided. В статье представлены основные принципы дизайна интерьера музеев по профилям и систематический порядок существующих 40 музеев Еревана. Включенные профили музеев, соответственно являются: художественные, исторические и археологические, естественные, технические, мемориальные, архитектурные, комплексные. Основные принципы дизайна интерьера музея, безусловно, различаются в каждом профиле и требуют различных подходов к проектированию для обеспечения необходимых функций. в целом, каждый профиль диктует презентацию, сохранение, безопасность экспозиции, а так же планирование направления движения людей и многие другие профессиональные навыки, которые играют важную роль для создания полного дизайна. Таким образом, для правильной планировки дизайна интерьера музеев, предоставлены лучшие образцы всемирных музеев каждого профиля.
Keywords: Արվեստ; Թանգարաններ